(untitled) (Global Journal of Management and Business Research, 2013)
The Barron’s World’s Best CEO list has been published each year since 2005. While there are numerous studies concerning the post-announcement share price reaction to firms included on the list, this is a definitive study that looks at the issue of CEO replacement following the announcement of the CEO to the list. This study determines that firms that do not change CEOs perform better; firms with CEOs with shorter tenures have lower returns than those with CEOs with a longer tenure; the reason for the replacement matters in terms of future performance with negative reasons such as performance and mergers yielding lower returns; inside successors produce higher returns than outside successors; and CEOs who appear on the list five or more times show significantly higher results.